Pengaruh Brand Ambassador, Brand Image, Brand Awareness Dan Harga Terhadap Keputusan Pembelian - Ghifari, Lafiandrie Al; Wismantoro, Yohan; Cahya, Handy Nur; Setiawan, Aries (Universitas Islam Kadiri, 2025)
This study aims to analyze purchasing decision factors influenced by brand ambassadors, brand image, brand awareness, and price on Vondutch fashion products in Semarang City. The research approach uses a quantitative approach. The population consists of all customers who use Vondutch fashion products and the number of samples is set at 100 respondents based on the Lemeshow formula because the population is not known for sure. The data collection technique uses a questionnaire. The data analysis technique uses the SPSS application to test the proposed hypothesis. The results of the study explain that simultaneously and partially the variables of brand ambassadors, brand image, brand awareness, and price have a positive and significant effect on purchasing decisions.